Radiologische Manifestationen von Lungenerkrankungen bei COVID-19 - Heidinger, Benedikt H. (Radiologe, 2020)
CLINICAL ISSUE: Since its emergence in late 2019, the disease caused by the novel coronavirus, termed COVID-19, has been declared a pandemic by the World Health Organization. Reference standard for the diagnosis of COVID-19 is a positive reverse transcription polymerase chain reaction (RT-PCR) test. While the RT-PCR shows a high specificity, its sensitivity depends on the duration of symptoms, viral load, quality of the sample, and the assay used. STANDARD RADIOLOGICAL METHODS: Chest radiography and computed tomography (CT) of the chest are the imaging modalities primarily used for assessment of the lung manifestations, extent, and complications of COVID-19 pneumonia. PERFORMANCE: Sensitivity and specificity of chest radiography is low. While sensitivity of CT for detecting COVID-19 pneumonia is high—averaging around 90%—its specificity is low—between 25 and 33%. PRACTICAL RECOMMENDATIONS: Indications for imaging in patients with suspected or diagnosed COVID-19 infection should be carefully considered to minimize the risk of infection for medical personnel and other patients. Imaging, particularly CT, can assess disease extent, complications, and differential diagnoses. COVID-19 pneumonia typically presents with bilateral, subpleural areas of ground glass opacifications with or without consolidations. During the course of the disease features resembling organizing pneumonia can occur. Follow-up examinations after recovery from COVID-19 pneumonia should focus on fibrotic changes of the lung parenchyma.